A Cross-Disciplinary Approach to Language Support for First Year Students in the Science Disciplines : Resources. - Zhang, Felicia; Lidbury, Brett; Schulte, Jurgen; Bridgeman, Adam; Yates, Brian; Rodger, John (Australian Learning and Teaching Council (ALTC), 2011)
Set of four resources emanating from a project that addressed the language needs of a diverse student body by investigating and testing strategic approaches to learning and teaching in first year sciences. It was concerned with the acquisition of language specific to science and the implicit teaching of meta-cognitive skills required in science. The resources include a language difficulty survey instrument; questions and quizzes; physics concept surveys; and class exercises.